Molecular evidence of Macracanthorhynchus hirudinaceus (Pallas, 1781) in cockchafers in rural areas of Elazig, Türkiye - Celik, F.; Tekin, A. S.; Uslug, M.; Simsek, S. (Cambridge Univ Press, 2025)
The primary definitive host of the giant acanthocephalan, also known as the giant thorny-headed worm Macracanthorhynchus hirudinaceus (Pallas, 1781), is Sus scrofa. The definitive host ingests the parasite by consuming infected scarabaeoid or hydrophilid beetles. This study aimed to ascertain the presence of M. hirudinaceus in the intermediate hosts through molecular analysis. The cockchafers were collected from Elazig province of T & uuml;rkiye. A total of 30 pools, comprising 10 pools for each of three districts were obtained from cockchafers collected from 10 areas. The gDNA was isolated and PCR was conducted using specific primers which amplify the mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) gene of M. hirudinaceus. Then, the PCR-positive samples were sequenced, and phylogenetic and haplotype analyses were performed. A total of 300 cockchafer adults and/or larvae were collected for this study from different regions of three districts (Sivrice, Baskil, and Keban) in Elazig province of T & uuml;rkiye. No PCR band was observed in any of the samples in Sivrice (0%). However, a total of 16 samples (5.3%), 10 from the Baskil (10%) and 6 from Keban (6%), showed a PCR band of 491 bp. All sequences were confirmed as M. hirudinaceus. Two distinct haplotypes were detected at two points. Of the total number of sequences, twelve were found to consist of a single haplotype. One of the two haplotypes was comprised of 10 isolates, while the other included six isolates. This study is one of the limited studies on the molecular identification and haplotyping of M. hirudinaceus in cockchafers.
Keywords: Macracanthorhynchus hirudinaceus; cockchafers; sequence; haplotype